Centro cultural y ambiental: Intervención urbana en el Cerro de la Popa como espacio vital para la ciudad de Cartagena de Indias (2016)
The Hill of the Stern is the most important elevation of the city of Cartagena with 150 msmn, has an pproximate area of 80 hectares and is the only green lung in the middle of the populated city, and in his top a Heritage of the Nation preserves: The church of the Virgin of the Candlemas. Nevertheless it suffers from erosion, deforestation, informal housings, visual pollution, which they are consequences of the small one - for not saying void - urban dynamics. On having spoken about urban dynamics two defiitions are distinguished: the fist one refers to the construcciones, and develop as such, that in this case are the informal housings, invasions that every day appropriate more his skirts. In the second case, it refers to the urban mobility, and the ascension on the part of the persons to the hill. The urban mobility in the hill limits itself to the persons’ ascension on February 2 for motive of the employer holidays once a year - and some ‘chivas’ that rise occasionally - for lack of activities that motivate the persons to rise and visit the hill, so that his both landscape and tourist potentials meet undervalued. All that has allowed that companies of telecommunications illegally should install antennas of great height that contaminate visually the hill and consequently the National wealth. To solve the problematics fist there is realized an analysis of the case of study and his problematics, delimiting the scales of approximation, which determine three products that answer to the magnitude of the territory, before identifid; and that sustain in the theoretical, referential, historical and legal frame.